Streptococcal DNase B Is Immunologically Identical to Superantigen SpeF but Involves Separate Domains - Eriksson, Anna (American Society for Microbiology, 1999)
The previous suggestion that streptococcal superantigen SpeF might be identical to DNase B was confirmed in this study. Polyclonal SpeF-specific antisera were able to inhibit depolymerization of methyl-green DNA by DNase B. However, T-cell mitogenicity and nuclease activity appear to involve separate immune epitopes on SpeF, since sera with the capacity to neutralize the mitogenic activity of SpeF did not always inhibit the DNase activity.